On the Cauchy problem for a degenerate parabolic differential equation - Ahmed El-Fiky (International Journal of Mathematics and Mathematical Sciences)
The aim of this work is to prove the existence and the uniqueness of the solution of a degenerate parabolic equation. This is done using H. Tanabe and P.E. Sobolevsldi theory.